Ten Years of Altmetrics : A Review of Latin America Contributions (2021)
ABSTRACT: Altmetrics studies emerged ten years ago in the Global North context and after a few years spread around the world. The paper investigates who are the Latin American researchers, which topics are covered and the relationship between South and North in Altmetric Studies. This study combines global mapping, social networks analysis and Content Analysis, using Dimensions, VOSviewer and Iramuteq to measure co-authorship, bibliographic coupling and co-citation analysis and content analysis to identify topics and types of production in Latina America outputs on alternative metrics. Results (n=172) show the prominence of Brazil, Colombia and Mexico in altmetric research in Latin America. There is an internal national co-authorship, with a huge influence from the North as reference to Latin American altmetric studies, but with gradual recognition of Mexico and Brazil as leading exponents in the region. We identify main topics related to local issues and regional impacts and discussions about the social role of the university. We conclude that the landscape of science output on altmetrics is becoming multipolar. Latin America emerged as an alternative hub of altmetric studies, but it still depends on references and collaboration with central countries. We also observed an emerging discussion on critics about low covering of regional data and an innovative development of methodologies and technologies as alternatives to commercial platforms that provide data to evaluate the social impact of universities. Latin America altmetric community should invest in resources to strengthen regional collaboration.